2014
DOI: 10.1177/1365480213515800
|View full text |Cite
|
Sign up to set email alerts
|

School improvement plans and student achievement: Preliminary evidence from the Quality and Merit Project in Italy

Abstract: This study provides preliminary evidence from an Italian in-service training program addressed to lower secondary school teachers which supports school improvement plans (SIPs). It aims at exploring the association between characteristics/contents of SIPs and student improvement in math achievement. Pre-post standardized tests and text analysis of SIPs were performed regarding a sample of 248 schools (13,816 students) participating in the project. Results show differences in planning strategies: better school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Indeed, parents are important facilitators for the transmission of alcohol-related attitudes and rules ( Adolfsen et al, 2017 ), and the perceived legitimacy of parental authority regarding alcohol use is a relevant factor during early adolescence ( Jackson, 2002 ). As well, because of the strong association between peer alcohol use and individual drinking habits in student populations ( Kuntsche & Jordan, 2006 ), intervention programs should be carried out at the class and school level, thus overall contributing to better organisational health ( Caputo & Rastelli, 2014 ). Specifically, such interventions could promote peer education and group discussion about alcohol-related issues, so that peers may act as positive role models who can reinforce behavioural messages ( MacArthur, Harrison, Caldwell, Hickman, & Campbell, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, parents are important facilitators for the transmission of alcohol-related attitudes and rules ( Adolfsen et al, 2017 ), and the perceived legitimacy of parental authority regarding alcohol use is a relevant factor during early adolescence ( Jackson, 2002 ). As well, because of the strong association between peer alcohol use and individual drinking habits in student populations ( Kuntsche & Jordan, 2006 ), intervention programs should be carried out at the class and school level, thus overall contributing to better organisational health ( Caputo & Rastelli, 2014 ). Specifically, such interventions could promote peer education and group discussion about alcohol-related issues, so that peers may act as positive role models who can reinforce behavioural messages ( MacArthur, Harrison, Caldwell, Hickman, & Campbell, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, organizational support has been found to moderate the effect of workplace bullying on workers' workplace deviance and paranoia (8). Other studies also found support for the role of perceived organizational support in reducing emotional exhaustion and in improving personal accomplishment (two indicators of burn-out) in special education teachers (54,55). Also, studies have found that workers' affective commitment on the one hand is positively related to workers' self-efficacy and career adaptability (56) and on the other hand, is negatively related to workers' deviant behaviors (57).…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…Moreover, it is important to recognise in schools how a "toxic" environment that is characterized by teachers' paranoia and victimization may be behind their display of workplace deviance. Therefore, components of the psycho-social intervention for teachers should also address their workplace deviant behaviors and how they might negatively affect not only their relationships with staff, parents and students but the school environment, productivity and the students' achievement (55,60) and wellbeing. Teachers should be taught on how to behave ethically by role modelling positive and ethical behavior, thus impacting positively on students' academic achievement and well-being.…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…This allows for greater systematization and transparency in the analysis, as well as a reduction in the possible errors that the researcher may incur when having to analyze large amounts of data (Flores-Kanter & Medrano, 2019). The T-LAB text analysis tool used was the "Thematic analysis of elementary context" (Lancia, 2004), which represents a relevant method for qualitative inquiry in clinical, social and educational fields (Caputo, 2014(Caputo, , 2015Caputo, Giacchetta, & Langher, 2016;Caputo & Rastelli, 2014), which may provide useful insights also in the examination of psychotherapy related issues (Caputo, 2013). In more detail, through some statistical multidimensional techniques ( i.e.…”
Section: Text Analysismentioning
confidence: 99%